A Case of Ewing Sarcoma of the Bladder Presenting in Early Infancy. Issue 4 (May 2021) - Howe, Adam S.; Pearce, Jennifer; Lian, Fei; Ribbons, Lisa; Chumbalkar, Vaibhav; Nazeer, Tipu; Kogan, Barry A.
Abstract : A 6-week-old female presented with gross hematuria and was diagnosed with Ewing sarcoma of the bladder through ultrasound and cystoscopic biopsies, along with a negative metastatic workup. She was treated with transurethral resection, chemotherapy consisting of with vincristine, cycolphosphamide, doxorubicin, ifosfamide and etoposide, and partial cystectomy. After completing chemotherapy, the patient has been doing well with no evidence of disease. There have been 14 other cases, 4 pediatric, of Ewing sarcoma of the bladder reported. To our knowledge, our case is the youngest patient reported with this disease.